Copper(II) and cobalt(II) tetrazole-saccharinate complexes as effective catalysts for oxidation of secondary alcohols - Frija, Luis M. T. (2017)
Mononuclear Cu(II) and Co(II) complexes comprising 2-methyltetrazole-saccharinate bidentate N,N-chelating ligand have been synthesized for the first time and tested as homogeneous catalysts for oxidation of secondary alcohols in a solvent-free and microwave assisted protocol using aqueous tertbutyl hydroperoxide (TBHP) as oxidant. The developed catalytic system exhibits broad functional group compatibility, allowing efficient and selective conversion of a variety of secondary alcohols, including allylic ones, into the corresponding ketones. With typical 0.2 mol% content of the catalyst and under 20-50 W microwave irradiation, most reactions are complete within 10 min, presenting TONs up to 5.5 x 10(2) and TOFs up to 1.1 x 10(4)h(-1). No additives and co-oxidants have been used, while TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxyl) acts as inhibitor in most cases. A plausible reaction mechanism involving the new catalytic systems is outlined. (C) 2016 Elsevier B.V. All rights reserved.